2021
DOI: 10.1039/d1ra03772b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trypsin-induced limited hydrolysis on the structural, functional, and bioactive properties of sericin

Abstract: Sericin was hydrolyzed to a limited extent using trypsin, then the physicochemical, prebiotic, and antioxidative properties of the obtained hydrolysates were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The results showed that the MW of SH-HA using ultrasonicassisted hydrolysis were similar to the SH produced by protease from Bacillus halodurans SE5 or Alcalase and SH hydrolysed by trypsin. Furthermore, sericin extracted using Bacillus halodurans SE5 or Alcalase and hydrolysed using trypsin had MW values of 50 kDa, <15 kDa and <10 kDa, respectively, 45,46 whereas SH-HA using ultrasonic-assisted hydrolysis in the current study had protein bands in the range 20-37 kDa and at 15 kDa, indicating that the hydrolysis process with HA using ultrasonic assistance was as effective as enzymatic hydrolysis. In addition, this hydrolysis was cheaper than using enzymatic hydrolysis.…”
Section: Resultsmentioning
confidence: 58%
“…The results showed that the MW of SH-HA using ultrasonicassisted hydrolysis were similar to the SH produced by protease from Bacillus halodurans SE5 or Alcalase and SH hydrolysed by trypsin. Furthermore, sericin extracted using Bacillus halodurans SE5 or Alcalase and hydrolysed using trypsin had MW values of 50 kDa, <15 kDa and <10 kDa, respectively, 45,46 whereas SH-HA using ultrasonic-assisted hydrolysis in the current study had protein bands in the range 20-37 kDa and at 15 kDa, indicating that the hydrolysis process with HA using ultrasonic assistance was as effective as enzymatic hydrolysis. In addition, this hydrolysis was cheaper than using enzymatic hydrolysis.…”
Section: Resultsmentioning
confidence: 58%
“…Reports have shown that metal‐chelating peptides are usually composed of histidine, cysteine, serine, aspartic acid, or glutamic acid (Wang et al, 2012). The remarkably higher copper chelating activity of CSH, QSH, and RSH can be ascribed to the sericin unique amino acid composition which is rich in serine (32–34%) and aspartic acid (14–16%) (Omar et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Present work aimed to prepare bioactive and functionalized sericin conjugate by the introduction of flavonoids. In our previous study, we found that sericin hydrolysates exhibit better functional and bioactive properties than sericin (Omar et al, 2021). We selected quercetin, rutin, and sericin hydrolysate and studied the physicochemical, antioxidative, and anti-inflammatory activities of flavonoid-silk sericin hydrolysate conjugates.…”
mentioning
confidence: 99%
“…Sericin, a natural protein present in the degumming water from the silk industry, is recognized for its therapeutic benefits, especially in cosmeceutical applications [ 27 ]. Nevertheless, a broad peptide composition (~10–250 kDa) hinders sericin from precise therapeutic targeting and lessens its potency [ 28 , 29 , 30 ]. Optimal size distribution and specific sequences of amino acids influence the biological activity of natural proteins [ 31 ].…”
Section: Discussionmentioning
confidence: 99%